Diagnostic capacity of colposcopy and cytology in screening for uterine cervix - Chacón-Byrne, Silvia R. (2024)
Introduction: Cervical cancer is one of the neoplasms with the highest incidence in Peru. The great gap in access to primary care reflects the need for effective diagnostic tests. Objetives:  To evaluate the diagnostic capacity between colposcopic and cytological tests in the detection of cervix lesion in patients treated at the Alberto Leopoldo Barton Thompson Hospital Complex.  Objetives:  To evaluate the diagnostic capacity between colposcopic and cytological tests in the detection of cervix lesion in patients treated at the Alberto Leopoldo Barton Thompson Hospital Complex. Material and methods:  Study of diagnostic tests  that investigated patients who attended the cervical screening clinic of the Alberto Leopoldo Barton Thompson Hospital Complex. Sensitivity (S), specificity (E), predictive values, percentage of agreement and diagnostic odd ratio (ORD) were calculated. Results: 185 patients were studied. The Pap smear's S was 78.9%, its E was 23.2%. The S of colposcopy was 93.3%, its E was 15.8%. The OR for Pap was 1.13 (95% CI [0.53 – 2.41]) and for colposcopy it was 2.62 (95% CI [0.90 – 8.64]). Conclusions: Colposcopy and Pap would present similar diagnostic accuracy as diagnostic tests for cervical intraepithelial lesions. In this context, colposcopy would be more useful in making decisions for early treatment.